(untitled) (Research, Society and Development, 2024)
The climacteric is a natural phase in a woman’s life, characterized by hormonal changes. These changes occur due to decreased hormone production by the ovaries, resulting in symptoms such as hot flashes, mood swings, and menstrual irregularities. This transition can affect a woman’s quality of life and lasts a few years, until menopause. This six-stage exploratory literature review of the integrative literature aims to analyze several recent scientific studies on hormone therapy, aiming to elucidate the existing controversies about the risks and benefits of its use in postmenopausal women. Hormone replacement therapy (HRT) is a treatment that uses hormones to relieve menopausal symptoms, such as hot flashes and mood swings. Although it has been studied since the 1960s, HRT still generates debates among health professionals due to new scientific evidence and theories, causing uncertainty in women. Despite the controversies, hormone therapy remains an option to reduce the impacts of menopause and improve quality of life. Menopause is a natural phase of a woman’s life that requires care and attention. The decision on the most appropriate treatment should be individualized and based on reliable information.